Delivery systems for antimicrobial peptides and proteins: towards optimization of bioavailability and targeting - Costa, Joana R. (2019)
Antimicrobial peptides (AMPs) and proteins are produced by a wide range of organisms as important elements of their defense mechanisms, forming a large number of antimicrobial compounds that can be used to treat several human infections. The potential for the use of AMPs and antimicrobial proteins in therapeutics is growing, but their application is often limited, due to their poor physical and/or chemical properties. In recent years, several drug delivery systems have been proposed to carry such molecules, in an attempt to overcome the difficulties regarding their properties. However, no review has yet systematized the most relevant information on this subject. Therefore, this review summarizes the work that has been conducted to develop delivery systems for the transport and protection of AMPs and antimicrobial proteins, including their description and potential applications, while highlighting the opportunities for future research in this field.